Cancer‐related genes in the transcription signature of facioscapulohumeral dystrophy myoblasts and myotubes. Issue 2 (17th December 2013) - Dmitriev, Petr; Kairov, Ulykbek; Robert, Thomas; Barat, Ana; Lazar, Vladimir; Carnac, Gilles; Laoudj‐Chenivesse, Dalila; Vassetzky, Yegor S.
Abstract Muscular dystrophy is a condition potentially predisposing for cancer; however, currently, only Myotonic dystrophy patients are known to have a higher risk of cancer. Here, we have searched for a link between facioscapulohumeral dystrophy (FSHD) and cancer by comparing published transcriptome signatures of FSHD and various malignant tumours and have found a significant enrichment of cancer‐related genes among the genes differentially expressed in FSHD. The analysis has shown that gene expression profiles of FSHD myoblasts and myotubes resemble that of Ewing's sarcoma more than that of other cancer types tested. This is the first study demonstrating a similarity between FSHD and cancer cell expression profiles, a finding that might indicate the existence of a common step in the pathogenesis of these two diseases.